A mezőgazdaság jövője, avagy a fenntartható fejlődés esélyei az Alföldön - Süli-Zakar, István; Baranyi, Béla (Tér és Társadalom, 1996)
It is becoming more and more evident by now that the real losers of the process of relative economic and social deconcentration, starting after the systemic change, are the rural areas in the Great Plain. The decline of the villages outside urban agglomerations and dynamic spatial structural axes is almost unavoidable, as the future of the villages that only rely upon agriculture is very uncertain. Village houses in Hungary have small courts, which does not meet the demand of modern agriculture. It is expected thus that the dynamic centres of the Hungarian agriculture will be the farms and manors newly built on medium size and large estates, or the farms "inherited" from the agricultural co-operatives. Of course regions where self-sustaining small homesteads are dominant will exist for a long time, but their inhabitants will probably have a very low living standard. The most hopeless in the Great Plain is the situation of the large rural regions along the borders. Here we can find counties the larger part of which – together with their county centres – were given to Rorhania and Ukraine after World War I and only the smaller part of them remained in Hungary. The rural regions situated here had taken an active part in the geographical division of labour of the historical Hungary, although with varying weight, and their economic life (agricultural production) was mainly connected to the large market centres of the market line on the brink of the Great Plain (Arad, Nagyvárad, Szatmárnémeti, Munkács, Ungvár). The borders drawn by the Treaty of Trianon tore these integrated regional units of the economic life apart, leaving these rural areas without urban centres and consumer markets. The practice of regional development in the past few decades promoted the centralisation of capital and labour force. This investment policy hardly paid any attention to the development, of areas with marginal location, because it focused on the development of a few towns and spent most of its resources on them. The available resources only enabled the rapid development of selected centres (mainly county seats), at the same time, for conceptual reasons and because of the features of the capital-distributing mechanism, the development of the centres of slighter significance was strongly restricted, and the "basic" settlements were practically damned for a decline. The changing economic policy accelerated concentration in the Great Plain, too, and the centralised development resulted in an increase in the differences within the counties. Because of this, large rural regions along the borders got into a crisis situation (e.g. Middle Tisza Region, the Sárrét area, Tiszazug, Bodrogköz, Taktaköz). The fundamental structural and organisational transition, concomitant with the systemic change in economy, did not improve the situation, either. It is no wonder thus that large agricultural regions in the Great Plain, primarilj , the rural regions situated along the borders of Hungary or the county borders, will find extreme difficulties in getting out of the long-lasting process of impoverishment and they will only be able to do so with significant help from the outside.